Effects of the morphology and structure on the elastic behavior of (Ti,Si,Al)N nanocomposites - Carvalho, S. (2003)
(Ti,Si,Al)N nanocomposite coatings with different Ti, Si, Al contents, were deposited onto silicon and polished high-speed steel substrates, by r.f. and/or d.c. reactive magnetron sputtering. The stoichiometry of the films was investigated by electron probe microanalysis and Rutherford backscattering spectrometry (RBS). The density was derived by combination of RBS results and thickness measurements obtained by ball-cratering. For comparison purposes, the evaluation of the Young's modulus was performed by depth-sensing indentation technique and with the laser-acoustic technique based on surface acoustic waves (SAW). Results showed in some cases differences in Young's modulus measured by both techniques. The Young's modulus obtained by SAW correlates with the density values from RBS, however, this behavior is not visible for the results measured with the ultramicroindentation technique. Both techniques indicate a small increase of Young's modulus of (Ti,Al)N by incorporating Si into the matrix. However, this improvement only occurs for small Si content, whereas for high Si content the elastic parameter reduces until almost 300 GPa. The morphology of the coatings was investigated by scanning electron microscopy and correlated with the differences observed by both SAW and indentation techniques.